Comparison of Labial and Mechanical Interruption for Measurement of Aerodynamic Parameters - Chapin, William J.; Hoffman, Matthew R.; Rieves, Adam L.; Jiang, Jack J. (Journal of voice, 2011)
To directly compare the mechanical and labial interruption techniques of measuring subglottal pressure (P s), mean flow rate (MFR), and laryngeal resistance (R L). Thirty-four subjects performed 10 trials with both mechanical and labial interruption. P s and MFR were recorded, whereas R L was calculated by dividing P s by MFR. Coefficients of variation were calculated to compare intrasubject precision. A subset of 10 subjects performed the tasks twice with 30 minutes between sessions. Bland-Altman plots were used to determine intrasubject repeatability for each of the methods. Mechanical interruption produced coefficients of variation for P s, MFR, and R L of 0.0995, 0.127, and 0.129, respectively. Labial interruption produced coefficients of variation of 0.102, 0.147, and 0.169, respectively. P values were 0.824 for P s, 0.159 for MFR, and 0.043 for R L. The Bland-Altman plots revealed comparable repeatability between the two methods. The 95% confidence intervals of the Bland-Altman plots for mechanical interruption were (−0.050, 0.072), (−0.543, 1.832), and (−2.498, 10.528) for MFR, P s, and R L. Confidence intervals for labial interruption were (−0.018, 0.031), (0.057, 2.442), and (−3.267, 10.595) for MFR, P s, and R L. Mechanical interruption produced higher precision when measuring R L because of more reliable airflow measurements. Mechanical and labial interruption showed comparable repeatability. Further research into using mechanical interruption clinically is warranted.